Retificação de cerâmica de alumina relacionada com diferentes técnicas de lubri-refrigeração: convencional e mínima quantidade de lubrificacao - E Sousa, R. M. [UNESP]; Iceri, D. M. [UNESP]; Destro, R. S. [UNESP]; Oikawa, M. H. [UNESP]; Bianchi, E. C. [UNESP]; De Aguiar, P. R. [UNESP]; Fortug, C. A. (My University, 2011)
Nowadays, environmental concerns are causing companies to seek reduce the environmental impacts caused by them, while improving product quality and manufacturing processes. Therefore, much research is being developed in the machining area to examine the actual damage to the environment by utilizing different methods of lubrification and cooling. This study aimed to analyze the surface roughness of the machined part and the wear of the grinding wheel in the fl at grinding of alumina ceramics with two methods of coolinglubrification: The conventional method with a flow rate of 27.5 L/min and the method of the minimum quantity of lubrification (MQL) at 100 mL/h. With the obtained results it's possible to say that, for the same machining parameters of MQL and conventional techniques, the MQL technique used a much smaller amount of fluid and assured good results for the diametral wear of the grinding wheel. However, the superficial roughness of the piece was worse for the MQL method than the conventional cooling technique. These results showed that using alternative forms of lubrification to reduce the use of cutting fluid are possible, depending on which factors are most important to the process that is wanted. Accordingly, if the MQL technique was used, it would surely bring, on one hand, the benefits of the reduction of the problems of recycling and disposal the cutting fluid, but on the other hand, leads to a lower surface quality of the parts.
Grinding of alumina ceramics with different cooling and lubrification techniques: Conventional and minimum quantity of lubrification
Keywords: Ceramics; Cutting fluid; Grinding; MQL